Perinatal Administration of C-Phycocyanin Protects Against Atherosclerosis in apoE-Deficient Mice by Modulating Cholesterol and Trimethylamine-N-Oxide Metabolisms. Issue 12 (28th October 2021) - Coué, Marine; Croyal, Mikael; Habib, Marina; Castellano, Blandine; Aguesse, Audrey; Grit, Isabelle; Gourdel, Mathilde; Billard, Hélène; Lépine, Olivier; Michel, Catherine; Ouguerram, Khadija
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Gestational hypercholesterolemia concomitantly with a highly oxidative environment is associated with higher atherosclerosis in human and animal offspring. This work aimed to determine whether perinatal administration of a C-phycocyanin concentrate, a powerful antioxidant, can protect against atherosclerosis development in genetically hypercholesterolemic mice in adult life. Approach and Results: C-Phycocyanin was administered during gestation solely or gestation and lactation to apolipoprotein E-deficient mice. Male and female offspring were studied until 25 weeks old. Progenies born to supplemented mothers displayed significantly less atherosclerotic root lesions than control group in all groups excepted in male supplemented during gestation and lactation. Female born to supplemented mothers had a greater gallbladder total bile acid pool, lower secondary hydrophobic bile acid levels such as lithocholic acid, associated with less plasma trimethylamine N -oxide at 16 weeks old compared with control mice. Regarding male born to C-Phycocyanin administrated mothers, they expressed a higher high-density lipoprotein cholesterol level, more soluble bile acids such as β-muricholic acids, and a decreased plasma trimethylamine at 16 weeks old. Liver reduced-to-oxidized glutathione ratio were increased and liver gene expression of superoxide dismutase and glutathione peroxidase were significantly decreased in male born to gestational supplemented mothers. No difference in the composition of cecal microbiota was found between groups, regardless of sex. Conclusions: Our findings suggest a protective effect of perinatal antioxidant administration on atherosclerosis development in apolipoprotein E-deficient mice involving sex-specific mechanisms.